Older workers in the construction industry: results of a routine health examination and a five year follow up. Issue 10 (October 1996) - Arndt, V; Rothenbacher, D; Brenner, H; Fraisse, E; Zschenderlein, B; Daniel, U; Schuberth, S; Fliedner, T M
Abstract : OBJECTIVE: To describe the health status of older construction workers and the occurrence of early retirement due to disability or of mortality within a five year follow up. METHODS: Firstly, a cross sectional study was performed among 4958 employees in the German construction industry, aged 40-64 years, who underwent standardised routine occupational health examinations in 1986-8. The study population included plumbers, carpenters, painters/varnishers, plasterers, unskilled workers, and white collar workers (control group). Job specific prevalence and age adjusted relative prevalence were calculated for hearing loss, abnormal findings at lung auscultation, reduced forced expiratory volume, increased diastolic blood pressure, abnormalities in the electrocardiogram, increased body mass index, hypercholesterolaemia, increased liver enzymes, abnormal findings in an examination of the musculoskeletal system, and abnormalities of the skin. Secondly, follow up for disability and all cause mortality was ascertained between 1992 and 1994 (mean follow up period = 4.5 y). Job specific crude rates were calculated for the occurrence of early retirement due to disability and for all cause mortality. With Cox's proportional hazards model, job specific relative risks, adjusted for age, nationality, and smoking were obtained. RESULTS: Compared with the white collar workers, a higher prevalence of hearing deficiencies, signs of obstructive lung diseases, increased body mass index, and musculoskeletal abnormalities were found among the construction workers at the baseline exam. During the follow up period, 141 men died and 341 men left the labour market due to disability. Compared with white collar workers, the construction workers showed a 3.5 to 8.4-fold increased rate of disability (P < 0.05 for all occupational groups) and a 1.2 to 2.1-fold increased all cause mortality (NS). CONCLUSIONS: This study shows the need and possibilities for further health promotion in workers employed in the construction industry, targeting both work related conditions and personal lifestyle factors. Rehabilitation measures should be enforced to limit the rate of disability among construction workers.